Genome-Based Taxonomic Classification of Bacteroidetes - Hahnke, Richard L.; Meier-Kolthoff, Jan P.; García-López, Marina; Mukherjee, Supratim; Huntemann, Marcel; Ivanova, Natalia N.; Woyke, Tanja; Kyrpides, Nikos C.; Klenk, Hans-Peter; Göker, Markus (Frontiers in Microbiology, 2016)
The bacterial phylum Bacteroidetes, characterized by a distinct gliding motility, occurs in a broad variety of ecosystems, habitats, life styles and physiologies. Accordingly, taxonomic classification of the phylum, based on a limited number of features, proved difficult and controversial in the past, for example, when decisions were based on unresolved phylogenetic trees of the 16S rRNA gene sequence. Here we use a large collection of type-strain genomes from Bacteroidetes and closely related phyla for assessing their taxonomy based on the principles of phylogenetic classification and trees inferred from genome-scale data. No significant conflict between 16S rRNA gene and whole-genome phylogenetic analysis is found, whereas many but not all of the involved taxa are supported as monophyletic groups, particularly in the genome-scale trees. Phenotypic and phylogenomic features support the separation of Balneolaceae as new phylum Balneolaeota from Rhodothermaeota and of Saprospiraceae as new class Saprospiria from Chitinophagia. Epilithonimonas is nested within the older genus Chryseobacterium and without significant phenotypic differences; thus merging the two genera is proposed. Similarly, Vitellibacter is proposed to be included in Aequorivita. Flexibacter is confirmed as being heterogeneous and dissected, yielding six distinct genera. Hallella seregens is a later heterotypic synonym of Prevotella dentalis. Compared to values directly calculated from genome sequences, the G+C content mentioned in many species descriptions is too imprecise; moreover, corrected G+C content values have a significantly better fit to the phylogeny. Corresponding emendations of species descriptions are provided where necessary. Whereas most observed conflict with the current classification of Bacteroidetes is already visible in 16S rRNA gene trees, as expected whole-genome phylogenies are much better resolved.